Juridical Study for the Management of the Conservation Area of Mount Ciremai National Park (Juridical Study in the Context of Water Resources Conservation) - Parihah, Vera Siti; Nurhalizah , Maulidah; Erika , Eryu; Sutrisno , Endang; Harliyanto , Rois (Journal of Legal and Cultural Analytics, 2025)
The management policy of the conservation area of Gunung Ciremai National Park (TNGC) is based on a balance between ecosystem conservation and sustainable use of water resources. Method, The prescriptive legal study uses normative and empirical legal research methods, analytical descriptive specifications, and qualitative approaches. TNGC has a strategic role as a water resource provider for the region through regional regulations regulating water resources conservation in the Kuningan Regency Regional Regulation Number 13 of 2007. Still, this area faces ecological pressure due to forest encroachment, land conversion, and uncontrolled water exploitation. Implementing regulations governing the conservation and management of the area still faces obstacles, such as weak law enforcement, overlapping authority, and a lack of community participation. Conservation efforts are needed to strengthen multi-stakeholder collaborative legal instruments and participatory approaches involving local communities. This study emphasizes the importance of synchronizing national and regional regulations and ecosystem-based management to ensure water resources' sustainability for the community's welfare and the environmental sustainability of TNGC.